Postural stability and risk of fall of person with trilateral prosthesis / Fatin Athirah Azali - Fatin Athirah, Azali (2019)
Postural stability is defined as the ability to maintain an upright position. It comes in two forms, static and dynamic. Static postural stability is when you are standing and not moving while dynamic stability is when you are moving or doing specific movements. Amputees impair the ability to balance especially when trilateral amputation involved. By losing 3 limbs of the body, postural stability may affect and required specific kind of training for the amputee to do daily activity. Risk of fall also may high than normal persons as the balance are off than usual. The parameter used to measure the postural stability and indicate the risk of fall is postural stability index. Postural stability index includes the total of anterior/posterior stability index (APSI) and medial-lateral stability index (MLSI). These parameters can be measured using Biodex Balance System SD (BSS). In procedure of this study, subjects were undergone two tests of postural stability and Fall Risk tests. Ten normal subjects and one trilateral amputee subject participate in this study. Normal subjects do the procedure with two conditions. First condition is normal (N) which subjects in standing-up position and both hands at the sides. Second condition, normal subjects can’t use both (N/N) hand and dominant leg to impersonate trilateral amputee. Trilateral amputee also undergoes the procedure with 2 conditions which are with prosthetics (P) and without prosthetics (N/P). The postural stability index then compared between two conditions for normal subjects and trilateral amputee subject respectively. Also, subjects undergo the procedure on two levels of platform; less stable platform level 3 for normal subjects’ perusal and level 5 for amputee subjects’ perusal, more stable platform level 12 used on normal and amputee subjects. The study found that there’s difference in stability index on normal subject between normal condition and condition where can’t use both hands and dominant leg. The differences are identified for each platform. For platform 3 procedure on normal subject, the stability index with condition N/N is increase by 75% from stability index with condition N. Platform 12 procedure on normal subjects, stability index with condition N/N increase by 41% from condition N and on amputee subject, stability index for condition N/P increase by 33% than condition P. Procedure for platform 5 on amputee subject, condition N/P stability index increase by 50% than P condition. Fall Risk test also determined by stability index value which then compare between N condition and N/N condition for normal subject, P condition and N/P condition for amputee subject. Stability index in Fall risk test for normal subjects with N/N condition higher than N condition by increasing 71% while for amputee subject, N/P condition higher than P condition increase by 29%. The test claimed that a lower score is more desirable than a higher score means lower stability index more stable the person is and vice versa which concluded that normal person with normal condition have higher postural stability than trilateral amputee.